Application of multivariate statistical techniques for water quality characterization of Sarda Sagar Reservoir, India - Kumar, Prem; Saxena, K K; Singh, N Okendro; Nayak, Ashok K; Tyagi, B C; Ali, S; Pandey, N N; Mahanta, P C (Indian Journal of Fisheries, 2012)
Multivariate statistical techniques were applied to water quality dataset collected from Sarda Sagar Reservoir. The results revealed the usefulness of multivariate techniques for evaluation of input water sources and interpretation of large complex water quality dataset for effective management of water resources. The largest source of variation (25%) is contributed from physical water quality parameters. Additional inputs come from the second factor accounting for about 15%. The third factor, accounting for 14% is associated with wastewater discharges and the fourth factor accounting for 12%. Finally, it suggests that a fraction of wastewater discharge is the only primary source of variations in this reservoir and there is no major threat of pollution. Cluster analysis showed that number of sampling sites as well as the sampling frequency could be consolidated.